HUBUNGAN KELINCAHAN DAN KOORDINASI MATA DAN KAKI DENGAN KEMAMPUAN DRIBBLING PADA SISWA EKSTRAKURIKULER FUTSAL SMP NEGERI 8 PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The purpose of this study was to determine the relationship between agility, the relationship of coordination and the relationship between eye and foot agility and dribbling ability in extracurricular students at SMP Negeri 8 Pekanbaru. The research was conducted in the field of SMP Negeri 8 Pekanbaru on February 25, 2020. This research used total sampling, namely all futsal extracurricular participants at SMP Negeri 8 Pekanbaru, totaling 20 people. Based on the results of the research that the author has described in the previous chapter, the following conclusions can be drawn: There is a relationship between agility and dribbling skills, where rtab is at a significant level α (0.05) = 0.456 means rcount (0.85)> rtab ( 0.456). Then there is a relationship between ankle coordination and dribbling skills, where rtab is at a significant level α (0.05) = 0.456, meaning rcount (0.90)> rtab (0.456), and there is a joint relationship between agility and eye coordination foot on the dribbling ability of the futsal team at SMPN 8 Pekanbaru, where rtab is at the significant level α (0.05) = 0.456, meaning Rhitung (0.901)> rtab (0.456).Key Words: Relationship, agility, eye and leg coordination, dribbling